2020
DOI: 10.1080/14783363.2020.1848422
|View full text |Cite
|
Sign up to set email alerts
|

On the inclusion of sustainability and digitalisation in quality management – an overview from past to present

Abstract: The aim of this study is to explore whether trends in sustainability and digitalisation from the 1980s until today have left any significant practical or epistemological footprints on the quality management paradigm. The study design consists of a mixed-methods approach that applies a data-mining methodology and content analysis to the digital archives of eight scientific journals: six within the quality management (QM) domain and two with a focus on operations management (OM). The data set contains an unbroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 81 publications
1
24
0
1
Order By: Relevance
“…Quality management is omnipresent in this industry, and a connection can be made between quality management and sustainable use of land. Carnerud et al [218] show changes over the past 40 years in how IT has influenced the recent trend toward sustainability and thereby changed contact quality management.…”
Section: Sdg 15: Life On Landmentioning
confidence: 99%
“…Quality management is omnipresent in this industry, and a connection can be made between quality management and sustainable use of land. Carnerud et al [218] show changes over the past 40 years in how IT has influenced the recent trend toward sustainability and thereby changed contact quality management.…”
Section: Sdg 15: Life On Landmentioning
confidence: 99%
“…Nonetheless, digitization in quality management is an ambiguous topic. Although digitization is identified as an area of particular interest to quality professionals, Carnerud et al (2020) failed to demonstrate academic attention on the connection to quality management studies. The authors observed indirect references to digitization in studies discussing information technology (IT) or information systems (IS).…”
Section: Total Quality Service and Digitalizationmentioning
confidence: 99%
“…As stated by Carnerud et al (2020), digitalisation has not been addressed in the scholarly quality management literature, and the quality management field is not addressing the full potential of digitalisation. Quality management practitioners have not yet seized the potential of digitalisation and are having difficulty with the implementation of digitalisation because they do not know where to start (Legner et al, 2017).…”
Section: Ijlssmentioning
confidence: 99%